THE PERFORMANCE OF BALI CALVES RESULTED FROMARTIFICIAL INSEMINATION USING SEMEN FROM DIFFERENT BALI BULLS - M., Dewantari; Oka, A. A. (Majalah Ilmiah Peternakan; Vol 23 No 1 (2020): Vol. 23 No.1 (2020), 2020)
Artificial insemination (AI) is one of the reproductive technologies that has succeeded in improving the genetic quality of livestock, and in a short time can produce calves in good quality in large numbers by utilizing superior males. This study aims to determine the performance of bali calves from artificial insemination using semen from different bali bulls. The study used primary and secondary data. Secondary data in the form of birth weight records of cows resulting from artificial insemination and primary data is a measurement of the weight and dimensions of the body of calves produced by artificial insemination from different bulls. Descriptive statistics are used to describe the actual condition of the productive potential of the bulls which is used as a source of cement in order to obtain basic data on the productive potential. The results showed that there were no differences in birth weight of calves from different bulls, as well as the body weight and dimensions of pre-weaning calves produced by artificial insemination from different bulls. The conclusion is that the bulls were used in this study have the same quality.